Enacting Social Control to Encourage Healthier Partner Diet and Exercise Behavior: Considering the Roles of Constraints and Topic Avoidance. Issue 5 (20th October 2019) - Ray, Colter D.; Burke, Tricia J.; Young, Valerie J.; Curran, Melissa A.
ABSTRACT: A multiple goals framework examined romantic couples' use of social control, perceived constraints to using social control, and topic avoidance regarding their health behaviors. Results showed a positive association between perceptions of social control constraints and use of negative social control. Additionally, topic avoidance was negatively related to the use of positive and negative social control and partners' health behaviors. Finally, the use of positive social control was positively associated with one's own health behaviors. These results illustrate how one's consideration of secondary goals affects the pursuit of the primary goal of influencing health behaviors. Specifically, romantic partners who discuss dieting and exercising should consider using positive social control when encouraging partners to engage in healthy behaviors.